Rapid screening, identification, and purification of neuraminidase inhibitors from Lithospermum erythrorhizon Sieb.et Zucc. by ultrafiltration with HPLC–ESI‐TOF‐MS combined with semipreparative HPLC. Issue 11 (28th April 2016) - Zhang, Minmin; Zhao, Hengqiang; Zhao, Zhiguo; Yan, Huijiao; Lv, Ruimin; Cui, Li; Yuan, Jinpeng; Wang, Daijie; Geng, Yanling; Liu, Daicheng; Wang, Xiao
Abstract : We put forward an efficient strategy based on bioassay guidance for the rapid screening, identification, and purification of the neuraminidase inhibitors from traditional Chinese medicines, and apply to the discovery of anti‐influenza components from Lithospermiun erythrorhizon Sieb.et Zucc. Ultrafiltration with high‐performance liquid chromatography and electrospray ionization time‐of‐flight mass spectrometry was employed for the rapid screening and preliminarily identification of anti‐influenza components from Zicao. Semipreparative high‐performance liquid chromatography was used for the rapid separation and purification of the target compounds. NMR spectroscopy, mass spectrometry, and UV spectroscopy were used for further structural identification, and the activity of the compounds was verified by in vitro assay. Five compounds were found to have neuraminidase inhibitory activity by this method. Subsequently, the five compounds were separated by semipreparative high‐performance liquid chromatography with the purity over 98% for all of them by high‐performance liquid chromatography test. Combined with the NMR spectroscopy, mass spectrometry, and UV spectroscopy data, they were identified as alkannin, acetylalkannin, isobutyrylalkannin, β, β‐dimethylacryloylalkannin and isovalerylalkannin. The in vitro assay showed that all five compounds had good neuraminidase inhibitory activities. These results suggested that the method is highly efficient, and it can provide platform and methodology supports for the rapid discovery of anti‐influenza active ingredients from complex Chinese herbal medicines.